The effect of reciprocal technique according to the aspirations of the person (B) and (C) to learn some basic skills - Sabaa, Ahmed; Hamza, Mohammed (Journal of Physical Education, 2018)
The effect of reciprocal technique according to the aspirations of the person (B) and (C) to learn some basic skills The Aim of the study was to investigate the effect of the post-tribal test method on learning some of the basic skills of the intermediate students in the middle class (B) and (C) and to identify the effect of the post-test method between the two types of personality (B) (C) The experimental method (the design of the experimental groups) for the two types of thinking (B) and (C). The sample consisted of a group of students of the intermediate stage of the second stage. 10 students were selected. The statistical bag (SPSS) (T-test of the associated and independent samples), the research concluded In the development of volleyball skills under study for students in the intermediate stage, the personality pattern (B) and (C) were found. There were no differences in the post-test results in the development of volleyball skills under study for middle school students between the personal models (B) C), and recommended the need to conduct studies include the variables of the current study or other and on the broader and comprehensive samples and other methods for most of the stages of schooling for males and females in Iraq.